Cross-Cultural Design Methods, Practice and Impact 7th International Conference, CCD 2015, Held as Part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings, Part I - Rau, P.L.Patrick (Information Systems and Applications, incl. Internet/Web, and HCI, 2015)
The  two LNCS volume set 9180-9181 constitutes the refereed proceedings of the 7th International Conference on  Cross-Cultural Design, CCD 2015, held as part of the 17th International Conference on Human-Computer Interaction, HCII 2015, in Los Angeles, CA, USA in August 2015, jointly with 15 other thematically similar conferences. The total of 1462 papers and 246 posters presented at the HCII 2015 conferences were carefully reviewed and selected from 4843 submissions. These papers  of the two volume set address as follows: LNCS 9180, Cross-Cultural Design: Methods, Practice and Impact (Part I), addressing the following major topics: cross-cultural product design, cross-cultural design methods and case studies, design, innovation, social development and sustainability and LNCS 9181, Cross-Cultural Design: Applications in Mobile Interaction, Education, Health, Transport and Cultural Heritage (Part II), addressing the following major topics: cultural aspects of social media and mobile services, culture for transport and travel, culture for design and design for culture, and culture for health, learning and games.